Quantitative Histomorphometry of Pre-ovulatory Follicles and Uterine Glands of Ongole-grade Heifer in Response to the Low Doses of PMSG Administration - K. B. Putro; A. Winarto; Amrozi; A. Boediono; W. Manalu (Tropical Animal Science Journal, 2023)
Injection of female mammalian animals with gonadotropin prior to mating using superovulation dose increases estradiol 17beta (E2) synthesis and secretion and improves the growth and development of the uterus to support prenatal growth with the side effect of increasing litter size. This experiment was designed to study the effects of low doses of PMSG injection in heifers on the growth of granulose cells (GC) of pre-ovulatory follicles, E2 synthesis, and uterine glands growth and development. Nine Ongole-grade heifers were divided into three groups of doses of PMSG injection, i.e., 0 IU/kg BW, 0.5 IU/kg BW, and 1.0 IU/kg BW. The injection of pregnant mare serum gonadotropin (PMSG) was conducted at the early stage of the second follicle wave. Blood samples were collected at estrus (day 0) to measure plasma E2 concentrations. The ovary and uterus were collected for histological observation after slaughtering the animal. The results showed that non-superovulation doses of PMSG injections at the second follicle wave significantly increased the growth of GC that eventually produced a significantly higher plasma E2 concentration by 39.47% and 113.57%, in heifers receiving 0.5 IU/kg BW and 1.0 IU/kg BW (p<0.05), respectively. The increase in E2 synthesis and secretion significantly stimulated the growth and development of uterine glands (p<0.05), which was reflected in the improved measures of uterine glands. In conclusion, injections of heifers with low doses of PMSG at the second follicle wave could increase the growth of GC to produce a higher secretion of E2 that eventually improves the growth and development of uterine glands in the endometrium without the risk of multiple calving.